Tetrachlorocarbonyliridates: water soluble carbon monoxide releasing molecules rate-modulated by the sixth ligand - Bikiel, Damian Ezequiel (2011)
A new family of compounds is presented as potential carbon monoxide releasing molecules (CORMs). These compounds, based on tetrachlorocarbonyliridate (III) derivatives, were synthesized and fully characterized by X-ray diffraction, electrospray mass spectrometry, IR, NMR, and density functional theory calculations. The rate of CO release was studied via the myoglobin assay. The results showed that the rate depends on the nature of the sixth ligand, trans to CO, and that a significant modulation on the release rate can be produced by changing the ligand. The reported compounds are soluble in aqueous media, and the rates of CO release are comparable with those for known CORMs, releasing CO at a rate of 0.03-0.58 μM min-1 in a 10 μM solution of myoglobin and 10 μM of the complexes. © 2011 American Chemical Society.